2014
DOI: 10.1002/ar.22781
|View full text |Cite
|
Sign up to set email alerts
|

Breathing in a box: Constraints on lung ventilation in giant pterosaurs

Abstract: Pterosaurs were the first vertebrates to achieve active flight, with some derived forms reaching enormous size. Accumulating fossil evidence confirms earlier indications that selection for large size in these flying forms resulted in a light, yet strong skeleton characterized by fusion of many bones of the trunk. However, this process also added mechanical constraints on the mobility of the thorax of large pterosaurs that likely limited the options available for lung ventilation. We present an alternative hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The transition of the parapophysis from the vertebral centrum to the transverse process has been well documented within crocodylians ( Claessens, 2009b ; Schachner et al, 2009 ), and also in fossil archosaurs ( Ewer, 1965 ; Piechowski and Dzik, 2010 ; Schachner et al, 2011 ; Geist et al, 2014 ). This bicondylar articulation is thought to act as a hinge joint ( Claessens, 2009b ), and so the cranial vertebral ribs would be expected to move mostly with pump and bucket handle motion, and the caudal ribs mostly with pump and calliper motion, although until now the explicit consequences of this shift for rib rotation have not been experimentally tested.…”
Section: Discussionmentioning
confidence: 97%
“…The transition of the parapophysis from the vertebral centrum to the transverse process has been well documented within crocodylians ( Claessens, 2009b ; Schachner et al, 2009 ), and also in fossil archosaurs ( Ewer, 1965 ; Piechowski and Dzik, 2010 ; Schachner et al, 2011 ; Geist et al, 2014 ). This bicondylar articulation is thought to act as a hinge joint ( Claessens, 2009b ), and so the cranial vertebral ribs would be expected to move mostly with pump and bucket handle motion, and the caudal ribs mostly with pump and calliper motion, although until now the explicit consequences of this shift for rib rotation have not been experimentally tested.…”
Section: Discussionmentioning
confidence: 97%
“…Pterosaurs, the ornithodiran outgroup to dinosauriforms, have been reconstructed as having an avian-style respiratory system based on the presence of unambiguous PSP and inferred air sacs [ 59 , 60 ]. Their costovertebral morphology has been described as ‘crocodilian-like', as the parapophysis migrates dorsally to lie on or at the base of the transverse process, and it has been suggested that pterosaurs therefore had more compliant, more homogeneous lungs [ 61 ]. However, the parapophysis also migrates dorsally towards the transverse process in many dinosaurian taxa, and our results showed greater similarity between dinosaurs and birds rather than dinosaurs and crocodilians.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the Chinese “tapejarids,” the presence of T-shaped wing phalanges have never been demonstrated for them, and it was explicitly stated that the lack of this feature exclude them from Azhdarchidae ( Lü et al 2006 : 321). SMNK 3843 was previously identified as a possible tapejaroid ( Frey et al 2003 : fig.1c), non-azhdarchid azhdarchoid ( Elgin and Campos 2012 ), or an azhdarchid ( Geist et al in press ). The scapulacoracoid of SMNK PAL 3843 has a coracoid flange rather than a tubercle and is more similar to that of azhdarchids ( Frey et al 2003 : fig.…”
Section: Review Of Localities Of Skeletal Fossils Of Azhdarmentioning
confidence: 99%